2022
DOI: 10.1039/d2ra04980e
|View full text |Cite
|
Sign up to set email alerts
|

Tracing carbonation in cementitious slurry using anthocyanin extracted from fresh or stale petals

Abstract: Anthocyanins extracted from flowers were prepared to trace carbonation in cementitious materials. For condition where a broad partial carbonated zone is presented, the new-developed indicator is more competitive over phenolphthalein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Toshio Honda et al [ 65 ] extracted three acylated cyanidin 3-sambubioside-5-glucosides (Orychophragonus violet-blue anthocyanins, OVAs) from the petals of O. violaceus , cyanidin3-[2-(2-(4-(6-(4-glucosylcaffeoyl)-glucosyl)-caffeoyl)-xylosyl)-6-(4-glucosyl-p-coumaroyl)gIucoside]-5-gjucoside,cyanidin3-[2-(2-(4-(6-(4-glucosylcaffeoyl)-glucosyl)-caffeoyl)-xylosyl)-6-(4-glucosyl-feruloyl)glucoside]-5-glucoside and cyanidin3-[2-(2-(4-(6-(4-glucosylcaffeoyl)-glucosyI)-caffeoyl)-xylosyl)-6-(4-glucosyl-sinapoyl)glucoside]-5-(6-malonylglucoside). A study [ 66 ] demonstrated that anthocyanins derived from the petals of O. violaceus have the potential to serve as an alternative to phenolphthalein in monitoring the carbonation process in cement paste and evaluating the long-term strength and resilience of concrete.…”
Section: Chemical Compositionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Toshio Honda et al [ 65 ] extracted three acylated cyanidin 3-sambubioside-5-glucosides (Orychophragonus violet-blue anthocyanins, OVAs) from the petals of O. violaceus , cyanidin3-[2-(2-(4-(6-(4-glucosylcaffeoyl)-glucosyl)-caffeoyl)-xylosyl)-6-(4-glucosyl-p-coumaroyl)gIucoside]-5-gjucoside,cyanidin3-[2-(2-(4-(6-(4-glucosylcaffeoyl)-glucosyl)-caffeoyl)-xylosyl)-6-(4-glucosyl-feruloyl)glucoside]-5-glucoside and cyanidin3-[2-(2-(4-(6-(4-glucosylcaffeoyl)-glucosyI)-caffeoyl)-xylosyl)-6-(4-glucosyl-sinapoyl)glucoside]-5-(6-malonylglucoside). A study [ 66 ] demonstrated that anthocyanins derived from the petals of O. violaceus have the potential to serve as an alternative to phenolphthalein in monitoring the carbonation process in cement paste and evaluating the long-term strength and resilience of concrete.…”
Section: Chemical Compositionsmentioning
confidence: 99%
“…Steroids have been reported for O. violaceus, see Figure 7 and Table 12. A study [66] demonstrated that anthocyanins derived from the petals of O. violaceus have the potential to serve as an alternative to phenolphthalein in monitoring the carbonation process in cement paste and evaluating the long-term strength and resilience of concrete.…”
Section: Steroidsmentioning
confidence: 99%